Platelet-to-Neutrophil Ratio and Efficacy of Remote Ischemic Conditioning in Acute Ischemic Stroke - Yu Cui; Ling-Yun Cui; Xia Chi; Qi Wang; Xian-Wen Zhang; Hui-Sheng Chen (PLoS ONE, 2025)
Background Remote ischemic conditioning (RIC) has been proven to improve neurologic function after stroke in RICAMIS trial. Aggravated thrombosis and inflammatory through interaction between platelet and immune cells affected the prognosis of stroke. We conducted an exploratory secondary analysis of RICAMIS to investigate whether platelet-to-neutrophil ratio (PNR) predicted efficacy of RIC in stroke. Methods Patients without protocol violation and with baseline blood routine examination from the full analysis set were included and divided into low PNR and high PNR subgroups. The primary outcome was 90-day excellent functional outcome defined as modified Rankin Scale score of 0–1. Compared with usual care alone, we investigated efficacy of RIC treatment in each PNR subgroup and their interaction. Results Of 1679 patients, 360 were assigned to low PNR and 1319 into high PNR. Compared with usual care alone, RIC treatment was associated with higher likelihood of 90-day excellent functional outcome across PNR, but significantly different in low PNR (60.9% versus 50.3%, adjusted RD, 11.3%; 95% CI, 1.1% to 21.5%; P =0.03) and not significantly different in high PNR (70.8% versus 65.3%, adjusted RD, 3.9%; 95% CI, −1.2% to 8.9%; P =0.13). No significant interaction was found (P =0.96). Conclusions This study firstly investigated the association between PNR at admission and efficacy of RIC treatment in stroke. With respect to long-term functional outcomes, patients benefited from RIC treatment regardless of PNR, but the benefit increased when level of PNR at admission was lower. Trial registration ClinicalTrials.gov Identifier: NCT03740971